Physicochemical properties of rainbow trout (Oncorhynchus mykiss) filet treated with high-voltage electrostatic field under different storage temperatures - Cheng, Yu-Tsung; Huang, Ping-Hsiu; Lu, Wen-Chien; Chu, Sheng-Che; Wang, Pei-Ming; Ko, Wen-Chien; Li, Po-Hsien (Frontiers in Sustainable Food Systems, 2023)
molecular protein composition. Moreover, the muscle tissue remained in excellent condition compared to storage at 25°C and 4°C. Additionally, there was no significant difference in the total viable count (TVC) and psychrophilic bacteria between storage at 0°C and 4°C, considered safe for food consumption. These promising findings are conveyed in a circular economy based on the food industry, particularly adequate raw materials, stable prices, measures to reduce food loss and waste, and contributing to developing efficient, diverse, and sustainable food processing systems.